The soft tissue profile of selected young adult Filipinos with normal occlusion - Joson, Christy A. (The Journal of the Philippine Dental Association)
The purpose of this study was to analyze the soft tissue relationships of 51 non-orthodontically treated young adult Filipinos (18-24 year of age) with normal occlusion, acceptable esthetics and good facial balance using Holdaway's analysis. The mean and standard deviation for each of the parameters were recorded and compared among age groups and according to gender. The combined male and female values showed a convex profile, small nose, an upper lip with slight excess curl, a lower lip that rolls our slightly beyond the H-line and a soft tissue chin that is a little fleshy. No significant differences were seen in the soft tissue variables of the subjects when grouped according to age. Five variable exhibited no significant difference and also five variables demonstrated highly significant differences between sexes. Chin thickness was found to be significantly larger in males than in females.